2009
DOI: 10.1111/j.1525-1446.2009.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Community/Public Health Nursing Practice Leaders' Views of the Doctorate of Nursing Practice

Abstract: Overall, there was much agreement among the practice leaders interviewed about the importance of a broad skill set for ANP in the specialty. However, the practice leaders interviewed here also identified the practical challenges involved in educating nurses at the DNP level in the C/PHN specialty, as well as some concerns about the definitions of ANP for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In particular, to match with the evolution of the healthcare environments and client care needs, the essential practice characteristics of AP nurses, including roles and responsibilities, have been constantly reshaping, leading to the need of AP nurses to continuously define and redefine the scope of their practice to administrators, healthcare professionals and clients to ensure clear understanding (Bonsall & Cheater 2008, Lewandowski & Adamle 2009). Corresponding education and legal issues surrounding the evolution of ANP have emerged, which require AP nurses to undertake higher levels of postgraduate nursing education and to work through the legislative systems to enact or amend regulations so as to enable the evolution of practice (Phillips 2009, Swider et al 2009). Such effort in redefining the scope of practice and working through the issues are considered as healthy, developmental and contributing to the professional development of nursing discipline, healthcare reform and cost containment (Sheer & Wong 2008, Pulcini et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, to match with the evolution of the healthcare environments and client care needs, the essential practice characteristics of AP nurses, including roles and responsibilities, have been constantly reshaping, leading to the need of AP nurses to continuously define and redefine the scope of their practice to administrators, healthcare professionals and clients to ensure clear understanding (Bonsall & Cheater 2008, Lewandowski & Adamle 2009). Corresponding education and legal issues surrounding the evolution of ANP have emerged, which require AP nurses to undertake higher levels of postgraduate nursing education and to work through the legislative systems to enact or amend regulations so as to enable the evolution of practice (Phillips 2009, Swider et al 2009). Such effort in redefining the scope of practice and working through the issues are considered as healthy, developmental and contributing to the professional development of nursing discipline, healthcare reform and cost containment (Sheer & Wong 2008, Pulcini et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…I and my colleague Dr. Pamela Levin have received three consecutive Health Resources and Services Administration grants (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) through the advanced education in nursing mechanism to support work to ensure that the Rush University curriculum was based on the national competencies for Public Health Nursing; to put the program online so that Public Health Nurses (PHNs) from across the country could access specialty study at the APHN level; to recruit nurses from underrepresented minority groups into the program; and to move the program to the practice doctorate level (Swider et al, 2006;Swider et al, 2009). The role of Erie was to bring quality primary care into communities and to partner with our communities to promote health.…”
Section: Pamela Clarke (Pc)mentioning
confidence: 99%
“…It should be stressed that during the initial discussions held by the AACN about the DNP, there was very little representation of the community and public health nursing organizations. The DNP movement was shaped more by those with a predominate focus on the direct care of individuals and families [4]. Thus, nursing leaders in community and public health did not see the immediate benefits to the requirement of the DNP to enter advanced practice nursing.…”
Section: Review Of Literaturementioning
confidence: 99%
“…While the nursing community generally agrees that the DNP degree will serve to strengthen nursing as an academic discipline, confusion remains regarding its impact on a more practical level. For example, for students wishing to pursue advanced practice education there is more than one entry point for DNP programs (post-baccalaureate or post-master's), curricula differs amongst institutions, consensus is lacking regarding appropriate certification, and certain advanced nursing practice organizations have concluded that the DNP is not a suitable terminal degree for their specialty and are not requiring it of their practitioners [2][3][4].…”
Section: Introductionmentioning
confidence: 99%